A method for spatio-temporal characterization of pulse beams with an all-optical image sensor. (April 2022) - Song, Yan; Peng, Bodong; Xu, Qing; Song, Guzhou; Yue, Zhiqin; Duan, Baojun; Han, Changcai; Yan, Weipeng; Yao, Zhiming; Ma, Jiming; Sheng, Liang; Li, Binkang
Highlights: The interaction of the electron beam with the all-optical image sensor has been simulated based on the Monte Carlo computational method for the first time. An InP-based all-optical image sensor was firstly applied in spatio-temporal characterization of pulse laser beams and paved the way for applications in electron and other particle beams. Fringes in the recorded images have been effectively removed with a filter method based on Fourier transformation. A differential method has been developed to increase the temporal resolution over the duration time of probe beams. Abstract: A method for analyzing the spatio-temporal intensity distribution of pulse beams, such as photons, electrons and other particles, with an all-optical image sensor has been developed. The image sensor measures the photon or particle intensity by probing the induced refractive index change due to their excitation in the semiconductor. In order to prove this scheme, the interaction of the electron beam with the image sensor has been simulated, indicating that the transient phase grating can be created in the semiconductor. The transient phase grating can be probed with a laser to evaluate the spatio-temporal intensity distribution of the incident electrons. In addition, an InP-based image sensor has been established for analyzing pulse laser beams. A pump-probe technique has been utilized to record images with varying delays between the analyzed and probe lasers and a differential method has been developed to improve the temporal resolution to be less than the duration time of probe lasers. Sequential images, representing the spatio-temporal distribution of the analyzed laser beams with several hundreds of picoseconds temporal resolution, have been obtained, indicating the ability of this scheme for analyzing the spatio-temporal distribution of pulse laser beams and paving the way for promising applications in characterization of pulse particle beams.